Dual Chemotherapeutic Loading in Oxalate Transferrin-Conjugated Polymersomes Incorporated into Chitosan Hydrogels for Site-Specific Targeting of Melanoma Cells - Mariana de C. Aranha; Luciana M. R. Alencar; Eliana B. Souto; Daniel T. Kamei; André M. Lopes (Pharmaceuticals, 2024)
In this work, we developed a smart drug delivery system composed of poly (ethylene glycol)-block-poly (ε-caprolactone) (PEG-PCL)-based polymersomes (Ps) loaded with doxorubicin (DOX) and vemurafenib (VEM). To enhance targeted delivery to malignant melanoma cells, these drug-loaded nanovesicles were conjugated to the oxalate transferrin variant (oxalate Tf) and incorporated into three-dimensional chitosan hydrogels. This innovative approach represents the first application of oxalate Tf for the precision delivery of drug-loaded polymersomes within a semi-solid dosage form based on chitosan hydrogels. These resulting semi-solids exhibited a sustained release profile for both encapsulated drugs. To evaluate their potency, we compared the cytotoxicity of native Tf-Ps with oxalate Tf-Ps. Notably, the oxalate Tf-Ps demonstrated a 3-fold decrease in cell viability against melanoma cells compared to normal cells and were 1.6-fold more potent than native Tf-Ps, indicating the greater potency of this nanoformulation. These findings suggest that dual-drug delivery using an oxalate-Tf-targeting ligand significantly enhances the drug delivery efficiency of Tf-conjugated nanovesicles and offers a promising strategy to overcome the challenge of multidrug resistance in melanoma therapy.